Peran Pengawasan Petugas Aviation Security Dalam Mendeteksi Ancaman Barang Berbahaya Di Bandar Udara Rahadi Oesman Ketapang - Sumiyati; Kifni Yudianto (Lembaga Pengembangan Kinerja Dosen, 2024)
; This research aims to find out: what the procedures are for checking the security of aircraft passengers and luggage transported by aircraft and individuals, so reliable human resources are needed. Therefore, airport operators have special units that carry out the role. an Aviation Security unit (AVSEC) which has a role as a unit that ensures airport security which is under the operational division. The Aviation Security Unit (AVSEC) must have a license as a standard of suitability in carrying out duties at airports, Avsec personnel always adhere to or are Fully guided by ICAO (International Civil Aviation Organization) regulations. This study used qualitative research methods. The data collection techniques used were observation, interviews, documents, and documentation along with observations. The researcher directly carried out observations, the researcher also explained the results of the data taken during interviews and observations. For the interview, the researcher interviewed Aviation Security officers from 3 sources with document data obtained by the researcher. from documentation of the activities of Aviation security officers when carrying out their duties and responsibilities in the field and also in the form of implementation documents for the data analysis techniques used, namely data collection, data reduction, data presentation, discussion, and conclusions. The role of aviation security officers is very important to support flight security. Officers must ensure that passengers' luggage entering the plane contains no prohibited items or items that endanger other passengers. This is because the responsibility of aviation security officers is very large and Avsec officers have carried it out. duties in accordance with existing procedures in the company. The implementation of standard operating procedures (SOP) is also very influential in improving employee performance where standard operational procedures are a guidebook and procedures for carrying out the work of each employee at each job desk.